Shaping competition legislation to the needs of small open economies : the case of CARICOM - Stewart, Taimoon (2004)
Argues that CARICOM countries would benefit from introducing competition legislation that includes prohibition of anti-competitive agreements, abuse of a dominant market position and merger control regulation.